2008
DOI: 10.1002/dmrr.819
|View full text |Cite
|
Sign up to set email alerts
|

Mutated ATP synthase induces oxidative stress and impaired insulin secretion in β‐cells of female BHE/cdb rats

Abstract: The findings are consistent with impaired but partially compensated mechanisms of insulin secretion early in life, but progressive non-compensated impairments due to oxidative stress occurs by age 43 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Dipeptidyl peptidase IV inhibitor (Millipore, Billerica, Mass., USA) was added to aliquots obtained at baseline and 30 min to assay gastric inhibitory polypeptide (GIP). Insulin tolerance test was conducted as published (Saleh et al 2008). Area under the curve and incremental area under the curve (IAUC) were calculated in accordance with established methods (Wolever 2004).…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
“…Dipeptidyl peptidase IV inhibitor (Millipore, Billerica, Mass., USA) was added to aliquots obtained at baseline and 30 min to assay gastric inhibitory polypeptide (GIP). Insulin tolerance test was conducted as published (Saleh et al 2008). Area under the curve and incremental area under the curve (IAUC) were calculated in accordance with established methods (Wolever 2004).…”
Section: Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
“…invadolysin larvae are defective in a behavioral response to hypoxia ROS are not only damaging molecules, but also have an important role in cell signaling Saleh et al, 2008). Mitochondria have and blw KG5893 third-instar fat body normalized to control tissue (wt).…”
Section: Acc Is Inhibited In the Invadolysin Mutantmentioning
confidence: 99%
“…It has also been reported that increased formation of oxygen radicals increases oxidative stress in the ATP synthase subunit a (ATP5a1) mutant rat. (Saleh et al, 2008).…”
Section: Loss Of Invadolysin Affects Mitochondrial Membrane Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some nuclear proteins, such as p300 and hepatocyte nuclear factor 4, are downstream targets of AMPK [4] . Saleh et al have reported [5] that pancreatic duodenal homeobox-1 (PDX-1) is one of the nuclear transcription factors that probably associates with AMPK to some extent. However, PDX-1 regulation by AMPK has not been confirmed in β cells.…”
Section: Introductionmentioning
confidence: 99%